Changes in the Rural Life in Belgorod Region in 2000-2013:Consequences of Economic Transformations - Efendiev, Azer; Sorokin, Pavel; Kozlova, Maria (Journal of Rural Development, 2015)
In the present paper, we analyse the key consequences of economic transformations in the rural territories in Belgorod region (Russia) which took place in the beginning of the XXIst century. We focus on the complex study of the changes in the rural life and on the way they are perceived by the local population. The paper is based on the results of the two studies conducted in 15 villages of Belgorod region utilising the same methodology. We reveal both positive and negative consequences of the economic transformations for the life of the rural population. The activities of large vertically integrated agricultural enterprises, so called "agroholdings" (launched in the last 10-12 years), contributed to the rapid growth of economic well-being but also caused several serious problems. The local population perceives agroholdings as aggressive intruders reconstructing traditional way of rural life by transforming local enterprises and enhancing unemployment and social inequality. Agroholdings are also seen as major obstacles for successful development of private farming in the region.